Susceptibility and synergism profiles of multi-drug resistant pseudomonas aeruginusa in an intensive care environment - Van Straten, A.M.S. (University of Pretoria, 2013)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2005.